Hypnerotomachia Poliphili – per un sincretismo culturale .......... 91 (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
This paper intends to analyse the idea of syncretism in Colonna’s work, a concept proposed as the conciliation of different cultural, intellectual, and religious experiences and expressed by the transgression crossing the limits of cultures and eras. In this article we propose to examine full-page figures included in the text. The first two and the last illustrations which describe the final stage of the main character’s journey, and contain key messages of Italian humanism concerning symbolic nature of objects, capable of revealing the connections between different cultures, remote in space and time are particularly interesting.